Гіпотермічне зберігання сфероїдів на основі мезенхімальних стромальних клітин за температури 22°C - Trufanova, Natalia; Trufanov, Oleh; Bozhok, Galyna; Revenko, Olena; Cherkashina, Daria; Pakhomov, Oleksandr; Petrenko, Oleksandr (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
Spheroids formed from mesenchymal stromal/stem cells (MSCs) provide optimal microenvironment for cell potential and stemmness support being also promising structures for relevant research models as well as cell therapies development. Practical application requires the development of effective methods for storing spheroids. Storage at ambient temperature (22°C) can be safer and more convenient for short term transportation of MSC-based spheroids. Herein we report that the spheroids formed by human adipose tissue-derived MSCs can be stored at ambient temperature (22°C) for up to 7 days with efficient preservation of viability, metabolic activity, ability to attach, and differentiation capacity. Cytoskeleton reorganization, cell size reduction, and metabolic activity decrease were shown to result from spheroidal formation and were extremely important for the development of spheroid resistance to the subsequent ambient storage. Probl Cryobiol Cryomed 2024; 34(2):186–200